Ruangguru: A Massive Indonesian Digital Platform as Assessment and English Learning Media - Lambok Hermanto Sihombing (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Ruangguru has become one of the most prominent digital education platforms in Indonesia, offering a wide range of interactive learning activities that effectively support students’ academic development. This study investigates the potential of Ruangguru as an assessment tool to enhance students’ self-learning competencies, particularly in English language learning. To achieve this objective, the study identifies the platform’s key features, pedagogical strengths, and its development over time. The analysis is supported by relevant research and informed by Manuel Castells’s theories on media technology and Stuart Hall’s reception analysis. The findings suggest that Ruangguru has significantly shaped Indonesian students’ perceptions of digital learning and demonstrates strong potential in fostering autonomous English learning through accessible, student-centered digital engagement.